A Pilot Study Evaluating 99mTc-anti-TNF-alpha Scintigraphy in Graves’ Ophtalmopathy Patients with Different Clinical Activity Score - Rebelo Pinto, E. dos S.; Lopes, F. P. P. L.; de Souza, S. A. L.; da Fonseca, L. M. B.; Vaisman, M.; Gutfilen, B.; dos Santos Teixeira, P. de F. (Hormone and Metabolic Research, 2013)
The present study describes the preliminary results of the use of 99mTc-anti-TNF-α scintigraphy as a new diagnostic approach to evaluate patients presenting with Graves’ ophthalmopathy (GO). Patients (n=25) presenting at different inflammatory stages of GO and 10 healthy volunteers underwent 99mTc-anti-TNF-α scintigraphy. Images were obtained 15 min after the intravenous injection of 370 MBq (10 mCi) 99mTc-anti-TNF-α. Planar images were obtained in a 256×256 matrix (each lasting 5 min) and single photon emission computed tomography (SPECT) scan lasting 13 min. Regions of interest (ROI) were drawn on the orbit and cerebral hemispheres. The uptake of 99m Tc-anti-TNF-α in these regions was compared and positive scintigraphy established when the ROI was >2.5. In addition, uptake for each positive exam was scored as either slight (2.6–5.1), moderate (5.2–7.6), or high (>7.6). In this pilot study, 69 orbits were evaluated (1 patient had only 1 eye), and 27 had a positive CAS (≥3/7). Scintigraphies were positive in 38 orbits. Comparing the results of the exams with CAS, a high sensitivity and negative predictive values were determined for scintigraphy (96.3% and 96.7%, respectively). However, the specificity and the positive predictive values were 71.4% and 68.4%, respectively, with an accuracy of 81.2%. The exclusion of examinations that were slightly positive from the analysis resulted in an improvement in test accuracy (95.5%). The preliminary results suggest that 99mTc-anti-TNF-α scintigraphy is a promising procedure for the evaluation of active orbital inflammation in GO.
Keywords: cytokines; radionuclide imaging; tumor necrosis factor-alpha; eye diseases; Graves disease; Graves ophtalmopathy